Ideational Matters in Essay Writing: EFL Undergraduates’ Perspectives - Amrina Rosyada; Januarius Mujianto; Sri Wuli Fitriati; Rudi Hartono (International Conference on Science, Education, and Technology, 2022)
Abstract. At higher educational levels, students/ learners experienced some difficulties in developing good writing. In expanding English writing academically, it is essential to analyze students’ writing development in several matters. This study aimed to ascertain difficulties in writing an essay on the students'/learners’ perspectives, particularly on ideational problems, and their expressions on that issue. By conducting a quantitative case study research design, this study engaged 37 third-year students at a private university in Jakarta who joined an academic writing course. In collecting the data, this study assigned a set of questionnaires and a Cause-and-Effect essay writing as the instruments. Based on the collated data and analysis, this study revealed six issues on ideational matters encountered by the students/learners in common, and each had different expressions of difficulties. Among the 37 writings, this study deeply narrated two remarkable essays with their statements. Hence, further research is needed to achieve an in-depth and comprehensive result.